Identity inferences: Implicatures, implications and extended interpretations. (November 2020) - Clark, Billy
This article considers how ideas from relevance-theoretic pragmatics can be applied in understanding the construction of identity in interaction, while presupposing that consideration of ideas about identity can make a significant contribution to pragmatic theories. While previous work on pragmatics has focused on the construction and performance of identity, this has not been much discussed in work from a relevance-theoretic perspective. For illustration, the article refers mainly to a video recording of a UK House of Commons Select Committee session on drug addiction. While the video provides considerable relevant data about identity construction, the article does not develop a detailed analysis of the video or the extracts it focuses on. Instead, it uses them to argue for the usefulness of relevance-theoretic ideas in understanding identity and impression management. The ideas focused on are that communication can be stronger or weaker (i.e. it can be more or less clear that particular assumptions are being intentionally communicated), that there is no clear cut-off point between very weakly communicated implicatures and non-communicated implications, that interpretation generally involves going beyond what the communicator intended to derive the addressee's own conclusions, that the effects of communicative interaction include more than the derivation of new assumptions and that adjustments to 'cognitive environments' (the sets of assumptions which are accessible to individuals at particular times) can continue after interactions take place. These ideas can be useful in a number of areas including in understanding identity in general, literary identities, attitudes to language varieties, the production of communicative acts and the teaching of spoken and written communication.